Audio-Visual-Based Query by Example Video Retrieval. (4th June 2013) - Hou, Sujuan; Zhou, Shangbo
Abstract : Query by example video retrieval aims at automatic retrieval of video samples which are similar to a user-provided example from video database. Considering that much of prior work on video analysis support retrieval using only visual features, in this paper, a two-step method for query by example is proposed, in which both audio and visual features are used. In the proposed method, a set of audio and visual features are, respectively, extracted from the shot level and key frame level. Among these features, audio features are employed to rough retrieval, while visual features are applied to refine retrieval. The experimental results demonstrate the good performance of the proposed approach.